Increasing High School Students' Understanding of Mathematical Concepts through the Discovery Learning Model Assisted by Powtoon - Lestari, Titin; Darta, Darta; Saputra, Jusep (Jurnal Pendidikan Amartha, 2024)
Mathematics demands a variety of abilities, including understanding mathematical concepts. However, reality shows that students have difficulty understanding mathematical concepts. This research aims to determine the increase in the ability to understand mathematical concepts with the Discovery Learning model assisted by Powtoon compared to ordinary learning models and determine the level of effectiveness. A quantitative approach with a quasi-experimental method and nonequivalent control group design was used in the research, with data collected through a written test of the ability to understand mathematical concepts. The research subjects were class XI students at SMA Pasundan 1 Bandung. The results of research data analysis show that students who studied with the Discovery Learning model assisted by Powtoon experienced a higher increase in understanding of mathematical concepts than students who studied with the regular learning model. The effectiveness of the increase is relatively large with this learning model. In conclusion, the Discovery Learning model assisted by Powtoon is very effective in improving the ability to understand mathematical concepts. Therefore, the Discovery Learning model assisted by Powtoon can be used as an alternative to improve the ability to understand mathematical concepts.